Nigeria Land Border Closure: Implication On Rice Smuggling And Local Production - Sherif. O. Aremu; Anthony Wende; Jonni Mahroza; Eko. H. Rizerius (CV. AFDIFAL MAJU BERKAH, 2023)
The foreign policy of a nation is framed to protect and stimulate its national interests in the execution of bilateral or multilateral relations with other nations. Foreign policy includes both choices and activities. These choices and activities comprise to some substantial level relations between one nation and others. Nigeria embarked on land borders closure as choice to protect her national interest against rice and other commodity smuggling. The objective of this study is to examine the border closure policy of the Nigerian government, as well as, relating it to the national interests of the nation, particularly in the areas of rice production, curbing arm proliferation, and smuggling. The study adopts qualitative research methodology, using explanatory approach to discuss the variables. The independent variable is Nigeria border policy and the dependent variable is rice smuggling activities. The study finds that rice production increased from 3.2 million tonnes to 6.4 million tonnes with a revenue earning of about US 2.6 billion in 2019 alone as against average revenue of US 18.3 million in 2011. Also, there are evidence showing that border closure saw a remarkable decrease in land border smuggling activities. The issue of arms proliferation was also put in check.